Pengaruh Media Dart Board Bio terhadap Hasil Belajar Peserta Didik pada Materi Sistem Pencernaan - Maradhy, Nabila Raqiqah; Maulana, Andi; Arif, Wiwin Pramita (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2023)
This research examines the influence of Dart Board Biomedia on the learning outcomes of students in the digestive system material for class XI at SMA 13 Makassar. The objectives of this research are: 1) to determine the learning outcomes of students in classes taught using textbooks, 2) to determine the learning outcomes of students taught using the Dart Board Biomedia, and 3) to determine the significant influence of Dart Board Biomedia on the learning outcomes. This study was a quasi-experimental research that employed a pretest-posttest control group design. Based on the results of the research conducted, the average score of student learning outcomes in the control class was in a good category with an average score of 65.78, while the average score of student learning outcomes in the experimental group was in the very good category with an average score of 88.34. It implied that there is a significant influence on the learning outcomes of students in the digestive system material using the Dart Board Bio media because the results of inferential data analysis in the one-sample test indicate that the achieved significance value is t-count 0.000 <0.05.